2019
DOI: 10.1089/hum.2018.178
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Curative Treatment of Beta Thalassemia: Cost-Efficacy Analysis of Gene Therapy Versus Allogenic Hematopoietic Stem-Cell Transplantation

Abstract: Seventy-five percent of patients with beta thalassemia (b-thalassemia) do not have human leukocyte antigen-matched siblings and until recently had no access to a curative treatment. Gene therapy is a promising treatment that can be proposed to these patients. This study estimates its cost and efficacy. In a monocentric retrospective study and cost-efficacy analysis, this study compared the two-year outcomes and costs of patients with b-thalassemia treated by gene therapy and hematopoietic stem-cell transplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 17 publications
(19 reference statements)
0
37
0
2
Order By: Relevance
“…The same strategy could be beneficial also in the case of -thalassemia, potentially providing a more economical gene therapy approach compared to the use of LV vectors to deliver a functional -globin gene. LV manufacturing is complex and very expensive (44). Our genome editing approach requires the delivery of RNA/protein reagents that might be less expensive than LV production and thus would allow the broader use of gene therapy for -hemoglobinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…The same strategy could be beneficial also in the case of -thalassemia, potentially providing a more economical gene therapy approach compared to the use of LV vectors to deliver a functional -globin gene. LV manufacturing is complex and very expensive (44). Our genome editing approach requires the delivery of RNA/protein reagents that might be less expensive than LV production and thus would allow the broader use of gene therapy for -hemoglobinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, we have so far treated nine dogs (five with EF1α-EGFP-2A-γC; two with both EF1α-EGFP-2A-γC and PGK-mCherry-2A-γC and two dogs with PGK-mCherry-2A-γC and G-CSF/AMD3100 mobilization) [5,6] and all treated dogs demonstrated efficacy and safety of FVV in-vivo gene therapy in canine model. Out of nine treated SCID-X1 dogs, five lived more than a year and three lived for over 2.5 years.…”
Section: Optimization Of Fvv In-vivo Gene Deliverymentioning
confidence: 99%
“…Therapies based on gene transfer to hematopoietic stem and progenitor cells (HSPCs) have achieved tremendous curative outcomes over the past decade and due to revolutionary success in some of these gene therapy clinical trials, these outcomes will redefine the clinical management of patients [1][2][3]. Pioneering gene therapy trials have shown that the genetic engineering of HSPCs can be a potentially superior alternative to allogeneic transplantation in the treatment of hematological monogenetic disorders including primary immunodeficiencies [4][5][6]. Transfer of therapeutic genes into long-term repopulating HSPCs can potentially cure blood disorders such as hemoglobinopathies and primary immunodeficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…With more than one sibling the chances will increase (e.g., 43.7% with two siblings), overall, only 30% of patients are able to find an HLA identical match within their family [28]. Indeed, 75% of betathalassemia patients do not have HLA matched siblings [29]. In the absence of a matched sibling, a matched unrelated donor may be identified in national or international registries.…”
Section: Pgt With Human Leucocyte Antigen (Hla) Matching: Clinical Utmentioning
confidence: 99%
“…The safety and efficacy of gene therapy have already been investigated for different pathologies such as β-thalassemia, sickle-cell disease, severe combined immunodeficiency, Wiskott-Aldrich syndrome, muscular dystrophy, and chronic granulomatous disease. However, a recent cost-efficacy analysis of gene therapy versus HSCT for β-thalassemia concluded that the preparation and procedure costs are currently higher for gene therapy [29]. Additionally, a longer follow-up is required so that, as anticipated, the longterm health benefits of gene therapy become evident.…”
Section: Future Prospectsmentioning
confidence: 99%